A Study On Internal And External Factors Influencing Manufacturing Company Share Price - Richie Alessandro Piero; Khairina Natsir (Jurnal Manajemen, 2023)
The Intention of the study is to discover academic proof associated with the role of internal factors such as Profitability, financial Leverage, and market value in driving a company's stock price. At the same time, this study wanted to evaluate the position of external factors, namely interest rates on stock price movements. The research population are companies in the manufacturing industry group, Indonesia Stock Exchange. By using a purposive-sampling its obtained a total of 280 company data from 56 manufacturing companies in the 2017 to 2021 time period. Data was analized using fixed effect regression model. The finding of the study show that Profitability is able to bring positive and significant movement to stock prices, financial leverageehas a positive anddinsignificant impact on stock prices, while market value has a negative and significantâ€ influence on stock prices, while interest rates significantly move stock prices in the opposite direction.